Upaya Nation Branding India sebagai Negara Tujuan Utama Destinasi Wisata Medis di Kawasan Asia Selatan pada Masa Pemerintahan Presiden Ram Nath Kovind - Aristiani, Desak Made Diah; Dewi, Putu Ratih Kumala; Wiranata, I Made Anom (Socio-political Communication and Policy Review, 2025)
During the administration of President Ram Nath Kovind, the promotion of medical tourism in India has been actively pursued by developing strategies and policies to position India as a leading global medical tourism destination, particularly in South Asia. However, India faces challenges ranging from the uneven distribution of healthcare facilities in rural areas to the increasing problem of air pollution. In fact, cities in India are ranked among the highest in global air pollution. This certainly worsens India's image as a country that provides healthcare facilities. The objective of this study is to describe the efforts made by India in building nation branding as a leading medical tourism destination in South Asia during the administration of President Ram Nath Kovind (2017–2022). The author uses two concepts to explain the efforts made by the Indian government, namely the concepts of nation branding and tourism diplomacy. The research method used is qualitative with data collection techniques in the form of library research, where data is obtained through analysis of relevant literature. The author found that the Indian government's nation branding efforts to become the leading medical tourism destination in South Asia were carried out through a series of policies, programs, and initiatives. This was done by focusing on the health sector and the environment as strategic instruments of tourism diplomacy, such as AYUSH medicine, the Ayushman Bharat Pradhan Mantri Jan Arogya Yojana program, Heal in India, and the National Clean Air Programme Abstrak Pada masa pemerintahan Presiden Ram Nath Kovind, promosi pariwisata medis India secara aktif digencarkan dengan mengembangkan strategi dan kebijakan untuk memposisikan India sebagai tujuan utama wisata medis global khususnya di kawasan Asia Selatan. Namun, terdapat tantangan yang harus dihadapi India, mulai dari permasalahan ketidak merataan fasilitas kesehatan di wilayah pedesaan hingga permasalahan polusi udara yang terus mengalami peningkatan. Bahkan, kota-kota di India tercatat menduduki peringkat tertinggi dalam pencemaran udara secara global. Hal ini tentu dapat memperburuk citra India sebagai negara penyedia fasilitas kesehatan. Adapun tujuan masalah dalam penelitian ini yaitu, mendeskripsikan upaya-upaya yang dilakukan India dalam membangun nation branding sebagai negara tujuan utama pariwisata medis di kawasan Asia Selatan pada masa pemerintahan Presiden Ram Nath Kovind (2017–2022). Penulis menggunakan dua konsep untuk menjelaskan upaya–upaya yang dilakukan pemerintah India, yaitu konsep nation branding dan diplomasi pariwisata. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data berupa studi kepustakaan (library research), data diperoleh melalui analisis literatur terkait. Penulis menemukan upaya nation branding pemerintah India untuk menjadi destinasi wisata medis utama di kawasan Asia Selatan dilakukan melalui serangkaian kebijakan, program, maupun inisiatif. Ini dilakukan dengan berfokus pada sektor kesehatan serta lingkungan sebagai instrumen diplomasi pariwisata yang strategis, seperti pengobatan AYUSH, program Ayushman Bharat Pradhan Mantri Jan Arogya Yojana, Heal in India, serta National Clean Air Programme. Kata-kunci : India, Kawasan Asia Selatan, Nation Branding, Ram Nath Kovind, Wisata Medis.